Improving resistance to drought in common bean in Mexico. - Acosta, Jorge; Acosta-Gallegos, Efraín; Padilla, Saúl; Goytia, María Antonieta; Rosales, Rigoberto; López, Ernesto (Agronomía Mesoamericana, 2015)
Since its inception in 1980, the breeding project for adaptation to drought has been based on crop phenology (escape or matching between biological cycle and water availability), and seed yield in multilocational trials under water stress conditions. For yield evaluation, bean genotypes were grouped on the basis of similar growth habits and phenology. Selection of segregating families according to adaptation to drought was postponed up until the F4 generation or subsequent ones, using incomplete block designs. Selection in early generations was based on moderate to high heretability traits such as biological cycle, grain phenology (color, size, shine), and reaction to diseases. Eight improved Durango bean varieties that are tolerant to temporary water deficits (Pinto Villa, Pinto Mestizo, Pinto Bayacora, Negro Altiplano, Negro Sahuatoba, Negro Durango, Bayo Victoria, and Azufrado Namiquipa) have been given to bean producers from Mexico’s semi-arid highlands. In 1998 seeds of two new varieties (Pinto Zapata and Flor de Mayo 2000) will be increased and registered. Their main traits are: type III indeterminate growth habits, short biological cycle, fast transition from vegetative to reproductive phase, and high yield rates.